HIGH FLOW AND LOW FLOW FREQUENCY ANALYSIS OF CIKAPUNDUNG RIVER - Suryadi, Cahya; Soekarno, Indratmo; Kardhana, Hadi; Kuntoro, Arno Adi (Universitas Muhammadiyah Palembang, 2023)
Climate change that occurs in Indonesia, especially in the upstream and middle Citarum areas is marked by changes in rainfall. In addition to the phenomenon of climate change, an increase in the number of people that occur in an area will have an impact on land cover changes that will affect river flow, so the dominant parameters that cause changes in the flow between changes in rainfall and land cover changes need to be reviewed. This study aims to determine the effect of changes in rainfall and land cover changes on flood discharge and the shift of flow duration curve. The author chose 4 SUH methods, namely SUH Nakayasu, SUH Soil Conservation Service (SCS), SUH ITB-1 and SUH Snyder-Alexejev to analyze high flow, and 2 methods, namely the F.J. Mock and NRECA methods to analyze low flow. The results of the research analysis are land changes that occur does not have a major impact on changes in the value of runoff coefficient, flood discharge analysis for Cikapundung-Pasirluyu sub-watersheds found that changes in flood discharge are dominated by changes in rainfall.